Investigating Peculiarities of Relationship between Parents and Adult - Katamadze, Davit; Beridze, Ketevan; Ketchakmadze, Rusudan; Meskhidze, Shorena (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Our research refers to investigation of peculiarities of relationship between parents and adult. This age is very actual because during this time physiological, physical and psychological changes take place that causes changes in relationship between parents and family members. We were interested in the fact that what do the parents think about their adult children, what problems they encounter during relationship and how they try to solve the challenges. This issue is actual not only in Goergia but in the whole world, that’s why we tried to study the issue deeply. We inquired adults and parents. With the parents we used “Varga test to investigate parent and child relationship”. For the adults, according to research goals, we created questionnaire. 160 parents and 185 adults participated in the research. Our research hypothesis was the following: We suppose that parent’s ideas and attitudes towards children affects the relationship between parents and adult.